Sustainable Tourism Development in China: An Analysis of Local Residents’ Attitudes Toward Tourists - Peng Gao; Zong-Yi Zhu (Tourism and Hospitality, 2025)
Scarce research on inbound tourism has focused on local residents’ attitudes toward inbound tourism, especially since the COVID-19 pandemic. This study combines social identity theory and emotional solidarity theory to explore Chinese residents’ attitudes toward inbound tourism. In particular, we explore two types of social identities (cultural and environmental identities, termed “humanistic environmental identity” in this study) and three factors of local residents’ emotional solidarity (welcoming nature, emotional closeness, and sympathetic understanding toward inbound tourists). Based on a survey of 310 local residents in Yangzhou, China, this study finds that local residents’ humanistic environmental identity significantly affects their emotional solidarity with inbound tourists, which significantly influences their acceptance of inbound tourism; this, in turn, increases their support for inbound tourism. Meanwhile, local residents’ humanistic environmental identity has an indirect effect on their support for inbound tourism through their welcoming nature, emotional closeness, sympathetic understanding, and acceptance of inbound tourism. In addition, local residents’ xenophobia significantly moderates the relationships between humanistic environmental identity and emotional closeness, between humanistic environmental identity and sympathetic understanding, and between emotional closeness and local residents’ acceptance of inbound tourism. This study extends research on factors affecting inbound tourism from the perspectives of local residents.